Risk factors for metastasis to No.14v lymph node and prognostic value of positive 14v lymph node for gastric cancer patients after surgery - Yue-Xiang Liang; Han Liang (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: Lymphadenectomy has been increasingly regarded as standard surgical procedure for advanced gastric cancer (GC), while necessity No.14v lymph node dissection for lower GC is still controversial. Methods: A total of 311 GC patients receiving D1+ (D1+7, 8a, 9) or D2 plus No.14v lymph node dissection in our center were enrolled. Patients were categorized into two groups based on No.14v lymph node status: positive group (PG) and negative group (NG). Results: Fifty patients (16.1%) had No.14v lymph node metastasis. Metastasis to No.4d, No.6 lymph node and distant metastasis were independent variables affecting No.14v lymph node metastasis. Patients with positive No.14v lymph node had a significant lower overall survival (OS) rate than those without (3-year OS, 34.0% vs. 67.0%, P<0.001). Conclusion: GC patients with positive No.4d and No.6 lymph node often metastasis to No.14v lymph node. Status of No.14v lymph node was an independent prognostic factor for GC staged TNM III. Patients with positive No.14v lymph node usually have a poor prognosis, while such patients without distant metastasis may benefit from a curative surgery.